COMPUTATIONAL INSIGHT INTO PIPER RETROFRACTUM CONSTITUENTS TARGETTING MAO-B IN PARKINSON'S DISEASE - Nur, Aisyah; Sri, Wahyuni; Kurnia Ulla, Aprilliana; Rifa Alya, Salsabilla; Nayla Maymuna, Fathin; Agus, Rusdin; Dhania, Novitasari (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2026)
Parkinson’s disease, characterized as a progressive neurodegenerative condition, represents a significant contributor to mortality in Indonesia. Piper retrofractum, a Piperaceae species rich in alkaloids, has been reported to contain compounds with neuroactive potential, similar to other Piper species in which Monoamine Oxidase-B (MAO-B) inhibition has been documented. However, no computational study has evaluated the interaction between Piper retrofractum bioactive compounds and MAO-B. = aimed to evaluate the MAO-B inhibitory potential of bioactive compounds from Piper retrofractum. Ten bioactive compounds from Piper retrofractum were screened and analyzed using Lipinski’s rules, PreADMET, pharmacophore modeling (Ligandscout 4.4.5), and molecular docking (AutoDock 4.2.6). The findings revealed that all test compounds met Lipinski's rule of Five. From the PreADMET results, Alismoxide showed a high Blood-Brain Barrier (BBB) crossing capacity of 4.59529. Trans-fagaramide was identified as the optimal pharmacophore match, displaying a fit score of 34.57. Meanwhile, from the molecular docking results, the most promising pharmacological candidate was piperolein-B, which formed a hydrogen bond with the amino acid residue LEU: A56, similar to the native ligand, with an inhibition constant of 0.015 μM and a binding energy of -10.6 kcal/mol. From these results, the bioactive compounds from Piper retrofractum can interact with the MAO-B receptor. These findings are computational predictions and require further experimental validation to confirm their potential for Parkinson’s disease treatment.